Secondary lymphedema of the arm, the perception of the disease, self-efficacy and depression as determinants of quality of life in patients with breast cancer - Popović -Petrović, Svetlana; Kovač, Aleksandra; Kovač, Nataša; Tovilović, Snežana; Novakov, Ivana; Ćulibrk, Dragana (Vojnosanitetski pregled, 2020)
Background/Aim. Secondary lymphedema of the arm is one of possible side-effects and complications of breast cancer and its treatment which can contribute and precipitate to a number of new psychosocial problems. The aim of this study was to examine the differences in quality of life of patients suffering from breast cancer, with arm lymphedema and those without lymphedema, and to determine the significance of the perception of the disease, depressive symptoms and self-efficacy contribution to overall quality of life. Methods. The research was designed as a cross-sectional study, which included 64 patients – 34 with arm lymphedema and 30 without lymphedema. Questionnaire FACT-B + 4 was applied to assess the quality of life, BIPQ for the perception of the disease, depression was measured by DASS-21 scale, while self-efficacy was tested by SGSE scale. T-test, Mann Whitney U Test, χ2 test and hierarchical regression analysis were applied to data processing. Results. There was not any significant difference between the groups in the total score of quality of life (t = 0.469, p > 0.05), or in the individual subscales: physical well-being (t = 0.535, p > 0.05), social/family well-being (t = 1.43, p > 0.05), emotional well-being (t = 1.35, p > 0.05), functional well-being (z = -0.243, p > 0.05), breast cancer scale (t = -0.839, p > 0.05) and arm scale (t = -0.514, p >0.05), while the perception of the disease (β = -0.603, t = -5.958, p < 0.001) and depression (β = -0.411, t = - 4.101, p
Keywords: breast neoplasms; women; upper extremity; lymphedema; quality of life; perception; depression.